Estresse e metas de socialização de pais de crianças com e sem transtorno do déficit de atenção e hiperatividade - TAVERNARD, Edimeire Pastori de Magalhães (Universidade Federal do Pará, 2019)
The behaviors that a person with ADHD has can cause a tangle of feelings within the family and within social, wearing their relations which can lead to rejection of that individual or even exclusion from the social group to which they are ligados.Esta research aimed to investigate the presence of stress and socialization goals of parents of children with and without ADHD. For this purpose, two studies were conducted. At first it was assessed the presence of stress in parents of children with and without ADHD and checked if there was correlation of these levels with attentional impairments and hyperactivity patterns / impulsivity of their children. In the second investigated the socialization goals and strategies of parents of children with and without ADHD. Participated in both estudos78 parents, divided into two groups: experimental group formed by parents of children or adolescentescom the diagnosis of ADHD and control group formed by parents of children without the diagnosis. Data were collected in a University Hospital and duasescolasregulares the public network in the city of Belém / PA. The instruments used were: Socio-Demographic Questionnaire, MTA-SNAP IV, Parenting Stress Index (PSI) .The first study results showed that the stress level of parents of children without ADHD (GC) was higher than that of parents of children with ADHD (GE) and the second study showed that parents of both groups have their main goals related to self-improvement, differing as the action strategies used to achieve the goals.